2014
DOI: 10.1126/science.1259652
|View full text |Cite
|
Sign up to set email alerts
|

Dysrhythmia in the suprachiasmatic nucleus inhibits memory processing

Abstract: Chronic circadian dysfunction impairs declarative memory in humans but has little effect in common rodent models of arrhythmia caused by clock gene knockouts or surgical ablation of the suprachiasmatic nucleus (SCN). An important problem overlooked in these translational models is that human dysrhythmia occurs while SCN circuitry is genetically and neurologically intact. Siberian hamsters (Phodopus sungorus) are particularly well suited for translational studies because they can be made arrhythmic by a one-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 35 publications
6
79
1
4
Order By: Relevance
“…41,42 However, SCN lesions rescue learning deficits in arrhythmic Siberian hamsters, suggesting that an arrhythmic master circadian clock in these animals actively inhibits memory consolidation. 43 Together, these results suggest that the circadian integrity of the neuronal network within the SCN is important for normal memory consolidation. In support of this view, we have previously shown that desynchrony of sleep stages in the forced desynchronized rat emerges from the desynchrony of specific neuronal subpopulations within the SCN.…”
Section: Discussionmentioning
confidence: 81%
“…41,42 However, SCN lesions rescue learning deficits in arrhythmic Siberian hamsters, suggesting that an arrhythmic master circadian clock in these animals actively inhibits memory consolidation. 43 Together, these results suggest that the circadian integrity of the neuronal network within the SCN is important for normal memory consolidation. In support of this view, we have previously shown that desynchrony of sleep stages in the forced desynchronized rat emerges from the desynchrony of specific neuronal subpopulations within the SCN.…”
Section: Discussionmentioning
confidence: 81%
“…Several animal models were applied to study the functional significance of circadian system, such as constant light exposure on rats (Fonken et al, 2012;Honma and Hiroshige, 1978), suprachiasmatic nucleus (SCN) ablation in Siberian hamsters (Bittman et al, 1991;Fernandez et al, 2014), and genetic modification of mice (Oliver et al, 2012;Vitaterna et al, 1994) and fruit flies (Konopka and Benzer, 1971;Simoni et al, 2014). Evidences indicated a strong correlation between circadian rhythms disruption and memory impairments in animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Circadian disruption through constant light conditions (Daan and Pittendrigh 1976) decreases performance in the Morris water maze along with hippocampal neurogenesis (Fujioka et al 2011). In wild-type hamsters with the SCN intact, induction of circadian dysrhythmia impairs spatial and recognition memory (Fernandez et al 2014). Acute experimental jet lag also disrupts recall of longterm contextual fear conditioning in mice (Loh et al 2010).…”
Section: Circadian Dysfunction and Memorymentioning
confidence: 99%
“…In rats, disinhibition of recurrent GABAergic inhibition is suggested as a mechanism for regulating circadian rhythmicity of LTP in hippocampal CA1 (Nakatsuka and Natsume 2014). In hamsters, circadian rhythmicity is necessary for declarative learning and memory as increased SCN GABAergic inhibition to the hippocampus in arrhythmic animals impairs memory (Ruby et al 2008(Ruby et al , 2013Fernandez et al 2014).…”
Section: Mechanisms Linking the Circadian Clock And Memorymentioning
confidence: 99%